Development and validation of machine learning models for prediction of nanomedicine solubility in supercritical solvent for advanced pharmaceutical manufacturing - Wenlin, L.; Ruijuana, Z.; Xiankuna, S.; Abdullahb, M.; Tazeddinovac, D. (Journal of Molecular Liquids, 2022)
Salsalate solubility in supercritical carbon dioxide was studied in this research by computational simulation to correlate the solubility to input parameters including temperature and pressure. A dataset was collected from resources and the models were correlated to the data. Both training and validation steps have been performed to implement the computational tasks. Indeed, we are dealing with a dataset with two P and T inputs and one output (drug solubility), and 32 data points. We chose three models based on Gaussian Process Regression (GPR) including simple (raw) GPR, Ada-boosted GPR, and Bagged GPR as two ensemble methods for correlation of the solubility data. All hyper-parameters were tuned for more general models and models evaluated with standard metrics. The GPR, Adaboost + GPR, and Bagging + GPR have scores of 0.9779, 0.9992, and 0.9795 using R-squared, respectively. Also, in terms of RMSE models have error rates of 1.25 × 10−4, 1.20 × 10−4, and 1.29 × 10−4, respectively. Finally, considering the standard criteria and visual analysis, the boosted GPR model is selected as the main model. The optimal values found as (P = 400, T = 338.0, Y = 0.003879) Растворимость сальсалатов в сверхкритическом диоксиде углерода изучалась в этом исследовании с помощью компьютерного моделирования, чтобы соотнести растворимость с входными параметрами, включая температуру и давление. Набор данных был собран из ресурсов, и модели были сопоставлены с данными. Для реализации вычислительных задач были выполнены этапы обучения и проверки. Действительно, мы имеем дело с набором данных с двумя входными данными Р и Т и одним выходным (растворимость лекарственного средства) и 32 точками данных. Мы выбрали три модели, основанные на регрессии гауссовского процесса (GPR), включая простой (необработанный) GPR, GPR с ускорением Ada и GPR с пакетами, в качестве двух ансамблевых методов для корреляции данных о растворимости. Все гиперпараметры были настроены для более общих моделей и моделей, оцениваемых по стандартным метрикам. GPR, Adaboost + GPR и Bagging + GPR имеют оценки 0,9779, 0,9992 и 0,9795 с использованием R-квадрата соответственно. Кроме того, с точки зрения моделей RMSE частота ошибок составляет 1,25 × 10–4, 1,20 × 10–4 и 1,29 × 10–4 соответственно. Наконец, с учетом стандартных критериев и визуального анализа в качестве основной модели выбрана усиленная георадарная модель. Оптимальные значения найдены как (P = 400, T = 338,0, Y = 0,00387
Keywords: скопус; импакт-фактор 2022; научный журнал; периодическое издание; дальнее зарубежье; зарубежное издание; зарубежные авторы; диоксид углерода